Sistem Klasifikasi Tingkat Kesesuaian Bibit Dan Pupuk Dengan Algoritma C4.5 Berbasis Website (Studi Kasus : Kecamatan Megaluh) - Panji Sulanggalih, Mochammad; Rohman Nudin, Salamun; Augusta Jannatul Firdaus, Reza (Inovate, 2021)
Selection of suitable seeds and fertilizers will greatly affect the level of plant fertility This research was conducted to classify the types of seeds and fertilizers accordingly, in order to obtain high levels of fertility and crop yields. The attributes used in this study were the type of seed, type of soil, type of pest, type of disease, and type of fertilizer. This study uses the Classification Decision Tree method with the C4.5 Algorithm, which is one of the methods in data mining. This method is used to obtain a set of tree-shaped patterns that can separate data classes from one another, which are used for decision making. The result of this research is a website-based system, so that it can be accessed by all users. This system can be used to classify the appropriate types of seeds and fertilizers based on the rules formed by the C4.5 calculation process. From the test results with the number of training data 499 data, the first root that was formed was fertilizer with a gain value of 0.142. The rule that is formed from the test results is that there are 173 rules that match, 120 rules are very suitable. And from 125 test data, there are 108 correct data and 17 error data, with the correct data percentage is 86.4% and the percentage of error data is 13.6%. Keywords : Classification, Decision Tree, C4.5 Algorithm, Agricultural Seed and Fertilizer, Website.